Adaptive responses of Gordonia alkanivorans IEGM 1277 to the action of meloxicam and its efficient biodegradation - Tyan, Semyon; Kostrikina, Nadezhda; Sorokin, Vladimir; Mulyukin, Andrey; Ivshina, Irina (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPharmaceutical contaminants such as meloxicam pose significant environmental risks due to their persistence and toxicity. The biodegradation potential of actinomycetes, particularly representatives of Gordonia, offers promising avenues for eco-friendly wastewater treatment. However, the ability of Gordonia to fully degrade meloxicam has not been previously demonstrated.MethodsThe biodegradation of meloxicam was investigated using G. alkanivorans IEGM 1277 as a model organism. Metabolite identification was performed using liquid chromatography-mass spectrometry (LC-MS). Candidate genes encoding meloxicam-oxidising enzymes were identified via genomic analysis. Adaptive bacterial responses to meloxicam exposure were characterised using atomic force microscopy (AFM), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDX).ResultsG. alkanivorans IEGM 1277 successfully decomposed meloxicam into primary metabolites, 5'-hydroxymethyl- and 5'-carboxymeloxicam, which exhibited reduced (eco)toxicity compared to the parent compound. Genomic analysis revealed several candidate genes potentially involved in meloxicam oxidation. Microscopic and spectroscopic analyses demonstrated significant phenotypic and metabolic changes in bacterial cells, indicating adaptive defence mechanisms triggered by meloxicam exposure.DiscussionThis study provides the first evidence of complete meloxicam biodegradation by Gordonia and elucidates the underlying enzymatic and adaptive cellular responses. The findings highlight the potential application of G. alkanivorans IEGM 1277 in developing efficient and environmentally safe biotechnologies for pharmaceutical wastewater treatment.